Features of monetary policy implementation in Ukraine - Sazonets, Igor; Сазонець, Ігор; Melnyk, Lesia; Мельник, Леся Леонідівна; Pushko, Ruslan; Пушко, Руслан; Gavrilko, Tetiana; Гаврилко, Тетяна; Krochak, Oksana; Крочак, Оксана; Mishustina, Tetiana; Мішустіна, Тетяна; et al. (My University, 2020)
The features of monetary policy implementation in Ukraine was analyzed in this work. There was shown the dependence of the Ukrainian currency market on migrant workers' remittances. The dollarization of the Ukrainian economics has a negative influence with it. However, a balanced approach is required to solve this problem. According to the authors' point of view, an important task of monetary policy in Ukraine is attracting free cash of individuals and enterprises in foreign currency into the banking system and into the real sector of the economy. The increasing process in international foreign reserves will enhance the stability of the national currency. У цій роботі проаналізовано особливості здійснення монетарної політики в Україні. Показана залежність українського валютного ринку від грошових переказів робітників-мігрантів. Доларизація української економіки має негативний вплив на це. Однак для вирішення цієї проблеми необхідний зважений підхід. На думку авторів, важливим завданням монетарної політики в Україні є залучення вільних грошових коштів фізичних осіб та підприємств в іноземній валюті в банківську систему та в реальний сектор економіки. Зростання процесу міжнародних іноземних резервів посилить стабільність національної валюти.
Особливості реалізації грошово-кредитної політики в Україні
Keywords: грошово-кредитна політика; monetary policy; валютна політика; currency policies; методи; methods; instruments of currency regulation; інструменти валютного регулювання; market; ринок